"We voted for your peace Santos; now it is our turn": a general strike, conflict, and the State in the Chocó, Colombia. Issue 2 (3rd May 2020) - Tubb, Daniel; Rojas, David Esteban
ABSTRACT: On 10 May 2017, a general strike began in the Chocó, Colombia. The strike paralyzed the region for 18 days. At issue was the Colombian government's failure to honor its promise to invest in social programs in one of Colombia's poorest and most marginalized departments. A month and a half later, on 27 June 2017, the Revolutionary Armed Forces of Colombia disarmed. What followed was not peace, at least not in the Chocó, but instead the transformation of an armed conflict which had lasted decades. When the guerrilla vacated the territories it had controlled, the Colombian State did not move in. Instead, two illegal armed groups took territorial control. Although the State is not absent in the department, a common misconception, it is incompetent at best or malevolent at worst. The strike read against the ongoing conflict shows that chocoanos see a more responsive State as part of the solution to the problems they face. These two arguments about the Chocó, first that the conflict transformed and second that there is a desire for a more responsive State, draw on a synthesis of mainstream Spanish-language media and descriptive shorts of events and situations taken from ethnographic fieldwork.